Synthesis and characterization of zinc oxide nanoparticles for dye-sensitized solar cells - Peukert, Wolfgang; Guldi, Dirk Michael; Hirsch, Andreas; Werner, Fabian; Gnichwitz, Jan-Frederik; Marczak, Renata (2008 AIChE Annual Meeting, AIChE 100, 2008)
Stable ZnO nanoparticles suitable for further derivatization of their surface were synthesized in the liquid phase from homogeneous ethanolic solutions of the precursors, lithium hydroxide and zinc acetate. The particle growth was monitored by in situ absorption spectroscopy and dynamic light scattering (DLS). It was found that the growth of the particles was governed by temperature as well as the presence of the reaction by-product lithium acetate during the ripening process. In particular, the reaction could be almost completely arrested by removal of this by-product. The "washing" consisted of repeated precipitation of the ZnO particles by addition of alkanes such as heptane, removal of the supernatant, and redispersion in ethanol. The ZnO nanoparticles, before and after "washing", were characterized by absorption spectroscopy, DLS, thermogravimetric analysis (TGA), X-ray powder diffraction (XRD) and high resolution transmission electron microscopy (HRTEM). The functionalization of the ZnO nanoparticles with photoactive organic compounds, i.e., 5-(N-(3,4-dihydroxyphenethyl)-2-phenoxyacetamide)-10, 15, 20-(p-tert-butyl-triphenyl)-porphyrinato-zinc and 5-(3,4-dihydroxy-N- phenylbenzamide)-10,15,20-tris(4-tertbutylphenyl)-porphyrinato-zinc, was examined. Mesoporous films of the ZnO nanoparticles suitable for use as electrodes in dye-sensitized solar cells (DSSCs) were prepared by the doctor blade technique. Following sintering the films were sensitized by the dye molecules mentioned above. The morphology of the films was characterized by using scanning electron microscopy (SEM). The current generated during photoelectrochemical measurements of these films was ascribed to an efficient photoinduced electron transfer from the photoexcited porphyrin to the ZnO moiety.
Keywords: functionalization; ZnO; nanoparticle; growth; light; scattering; solar; call